Chinese and Soviet aid to Africa - Weinstein, Warren (New York : Praeger Publishers, 1975)
This book grew out of a joint seminar held at the City Graduate Centre of the City University of New York in late May, 1973. Its purpose was to review and analyze the role Chinese and Soviet aid plays in Africa's political and economical development, and to provide for an exchange of views between academic and nonacademic specialists.
Includes bibliographical references.
usc 08/10/18
Loans
Keywords: Economic assistance, Chinese; Economic assistance, Soviet; Africa